Al-Madāris Al-Qurāniyyaħ Fī Al-Qarn Al-Ṡānī Al-Hijrī: المدارس القرآنية في القرن الثاني الهجري - Nabil Ahmed Tarmom; Adha Saputra (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2021)
The purpose of this study is to analyze the historical record and participation and contribution of qur'aniyah madrassas that exist in the second year of hijri. This research uses analytical descriptive methods by referring to and analyzing data from key sources directly related to the theme. As for the results of this study, there are at least five large madrassas that are central to the birth of qira'at expert priests as well as having an important role in the spread of qira'at science to various parts of the world. The first is the Kufiyah Madrasah in Kufa City which has the most qiraat experts, numbering one hundred and sixty-five of them there are Imam Ashim, Hamzah, Al Kisai, and Al A'masy. The second is the Bashriyah Madrassa in Basrah City with a number of qira'at experts seventy-nine, one of whom is Imam Abu 'Amr. The three Madaniyah Madrassas in the city of Madinah Al-Munawwarah whose number of qira'at experts reached fifty one of them was Imam Nafi. The fourth is the Makkiyah Madrassa in Mecca, the qira'at experts who settled here numbered forty-one. The fifth is the Shamiyah Madrassa in the Sham region which has forty-three qira'at members.